ASSESSMENT OF FACTORS AFFECTING SELECTION OF CIVIL CONTRACTOR (Global Journal of Advanced Engineering Technologies and Sciences, 2016)
Selection of a contractor is a key decision made by clients and the process of selection a contractor has become an important issue in construction projects. The need for achieving good contractor for the finished product in the construction projects is very important to meet the requirements of the clients. The factors affecting the selection of civil contractor for construction were identified based on literature review and interviews of government organization personnel. The data was collected by semi structured interviews and questionnaire survey of Government Organizations Amravati Region. This study is intended to identify the factors that affect the selection of civil contractor of construction projects and ranking them as per their degree of importance using Relative Importance Index Method (RII). The top five factors affecting the selection of civil contractor of construction projects are Finance, Experience, Health and Safety, Organization Capability and Quality. Meanwhile the Environment, Planning and Control, Resource these factors has been given the least importance amongst all the responding organizations.